The optimal level of deposit insurance coverage - Michael Manz (Federal Reserve Bank of Boston, 2009)
This paper develops a global game model that allows for a rigorous analysis of partial deposit insurance and provides the first comparative statics of the optimal level of deposit coverage. The optimal amount of coverage increases with lower bank liquidity requirements, with a higher precision of depositors' information, and with a lower relevance of large, uninsured creditors, and it should not be increased in anticipation of an economic downturn. Optimal insurance is higher if there is contagion and lower if banks can assume excessive risk, but interestingly, a high level of coverage may not be optimal even in the absence of moral hazard on the part of banks. The model supports the inauguration of coinsurance provisions and is applied to compare various policies addressing financial fragility. While an optimal lending of last resort policy can outperform deposit insurance, anticipated bailouts are inferior in terms of welfare. Capital requirements are not a substitute for insurance, but mitigate excessive risk taking.
Keywords: G21; G28; C72; 330; deposit insurance; level of coverage; bank runs; global games; systemic risk; moral hazard; coinsurance; Einlagensicherung; Bankenkrise; Theorie